Cardiovascular responses of beginner and advanced practitioners to different volume and intensity resistance exercise protocols. - Leandro Paes Ferreira; Osvaldo Costa Moreira; Lucas Rogério dos Reis Caldas; Leonardo Mateus Teixeira de Rezende; Kaitlin Hughes; Eduardo Souza; Miguel Araújo Carneiro-Júnior (Asociación Española de Ciencias del Deporte, 2020)
Introduction: The resistance exercise (RE) is recommended for whole population. However, some variables can promote different physiological responses during the performance, with a direct impact on cardiovascular responses. Thus, the objective was to verify the cardiovascular responses to three RE protocols between beginners (BG) and advanced (AD) practitioners. Methodsː thirty male resistance training practitioners divided into two groups: BG and AD. The volunteers were studied during three protocols of bench press exercise: 1:15 repetitions at 65% of 1RM; 2:8 repetitions at 80% of 1RM; 3:4 repetitions at 90% of 1RM. The systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR) and rate pressure product (RPP) were measured before and after the protocols. Resultsː there was a significant increase in HR, SBP, DBP and RPP from rest to post exercise. The AD subjects showed lower values of HR, SBP and RPP in the protocol 1 compared to 2 and 3; and presented higher values of HR and RPP in protocol 3 compared to 2. Discussionː the three protocols increased the cardiovascular overload compared to rest values, and no differences were observed between groups. In AD, the intensity seems to produce more cardiovascular overload than the volume or the total training load.